Digital Free Trade Zone in Facilitating Small Medium Enterprises for Globalisation: A Perspective from Malaysia Small and Medium Enterprises - Chin, Mui Yin; Foo, Lee Peng; Falahat, Mohammad (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The establishment of Digital Free Trade Zone (DFTZ) in Malaysia is closely related to the Chinese e-commerce giant. It was an initiative to spearhead Malaysia’s national e-Commerce strategic roadmap and empowering Small and Medium Enterprises (SMEs) to do cross-border commerce seamlessly. As such, this study aims to understand the perception of Malaysia SMEs towards DFTZ initiative and identify the hidden trepidation of Malaysia’s SMEs towards the e-commerce platforms via focus group interview as per Grounded Theory procedures. The findings reveal that about 40% of the interviewees are pessimistic about DFTZ and did not comprehend the potential benefit beyond it. Meanwhile, apart from incompatible cost structure and digital infrastructure development, lack of technical support knowledge and digital talent in innovative marketing strategies are among the main reasons the interviewees hesitate to move towards e-commerce platforms. Therefore, the authorities are urged to take several measures such as providing significant incentives for SMEs to upskilling their workforce, nurturing technology talent and ensuring the development of digital infrastructure to eliminate the trepidation that Malaysia SMEs currently faced. Be realistic and pragmatic when reviewing the capabilities of SMEs against the world factory is utmost important in helping SME to go global and remain competitive.